2016
DOI: 10.1073/pnas.1611797113
|View full text |Cite
|
Sign up to set email alerts
|

First genealogy for a wild marine fish population reveals multigenerational philopatry

Abstract: Natal philopatry, the return of individuals to their natal area for reproduction, has advantages and disadvantages for animal populations. Natal philopatry may generate local genetic adaptation, but it may also increase the probability of inbreeding that can compromise persistence. Although natal philopatry is well documented in anadromous fishes, marine fish may also return to their birth site to spawn. How philopatry shapes wild fish populations is, however, unclear because it requires constructing multigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 39 publications
(39 reference statements)
5
52
0
Order By: Relevance
“…polyacanthus are both demersal spawners which lay their eggs in caves, and kin recognition is potentially relevant to both species. For those species with a pelagic larval phase, studies have found a high proportion of larvae returning (∼50%), not only to their natal reef, but within metres of their parents at settlement (Jones , Salles et al ).…”
Section: Methodsmentioning
confidence: 99%
“…polyacanthus are both demersal spawners which lay their eggs in caves, and kin recognition is potentially relevant to both species. For those species with a pelagic larval phase, studies have found a high proportion of larvae returning (∼50%), not only to their natal reef, but within metres of their parents at settlement (Jones , Salles et al ).…”
Section: Methodsmentioning
confidence: 99%
“…The orange clownfish is used as a model species to study patterns and processes of social organization (Buston & Wong, 2014;Buston, Bogdanowicz, Wong, & Harrison, 2007;Wong, Uppaluri, Medina, Seymour, & Buston, 2016), sex change (Buston, 2003), mutualism (Schmiege, D'Aloia, & Buston, 2017), habitat selection (Dixson et al, 2008;Elliott & Mariscal, 2001;Scott & Dixson, 2016), lifespan (Buston & García, 2007) and predator-prey interactions (Dixson, 2012;Manassa, Dixson, McCormick, & Chivers, 2013). It has been central to ground-breaking research into the scale of larval dispersal and population connectivity in marine fishes (Almany et al, 2017;Pinsky et al, 2017;Planes, Jones, & Thorrold, 2009;Salles et al, 2016) and how this influences the efficacy of marine protected areas (Berumen et al, 2012;Planes et al, 2009). It is also used to study the ecological effects of environmental disturbances in marine ecosystems (Hess, Wenger, Ainsworth, & Rummer, 2015;Wenger et al, 2014), including climate change (McLeod et al, 2013;Saenz-Agudelo, Jones, Thorrold, & Planes, 2011) and ocean acidification (Dixson, Munday, & Jones, 2010;Jarrold, Humphrey, McCormick, & Munday, 2017;Munday et al, 2009;Simpson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential for kin disruption, genetic studies have shown that, across major taxonomic groups, pairs of putative siblings, and even family groups, are sometimes found within the same microhabitat or sampling location after settlement (Iacchei et al 2013, Salles et al 2016, Selwyn et al 2016, Riquet et al 2017). These findings challenge conventional views of kinship in the sea and raise questions about how kin associations persist despite the potential for dispersal to disrupt them.…”
Section: Introductionmentioning
confidence: 99%
“…These patterns all support the notion that long-distance dispersal and gene flow can be common in the marine environment. Nevertheless, genetic parentage studies have revealed limited dispersal in some species (D'Aloia et al 2015, Salles et al 2016; therefore, it remains a plausible explanation for marine kin structure.…”
Section: Introductionmentioning
confidence: 99%